Biological kinetics of candida albicans clinical strains filmforming in patients with bronchopulmonary complications of traumatic spinal cord disease - V Yu Ul’yanov; V V Shchukovskiy; I A Norkin; S V Opredelentseva; G A Drozdova (RUDN Journal of Medicine, 2014)
The intensity of 10 C. albicans clinical strains filmforming in patients with bronchopulmonary complications of early traumatic spinal cord disease was studied in statistic condition of flatbed culture on the 1 st, 2 nd, 3 rd, 4 th and 5 th days. It was specified that life cycle of C. albicans has phase character and is characterized by quantitative changes in the intensity of its filmforming.